TEACHING THE ENGLISH LANGUAGE WITH MODERN TECHNOLOGIES AND WEBSITES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article is about the role of modern technology and websites in English language teaching, as well as successful approaches to foreign language teaching.